Seismic Performance Evaluation of an Existing Laboratory Building with Concrete Strength Degradation Using Tier 3 Response Spectrum Analysis Based on ASCE 41-17 - Aditya Rihadatul Aisy; Josia Irwan Rastandi; Jessica Sjah (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Indonesia is located in a region with high seismic activity. The high frequency of earthquakes in Indonesia poses significant challenges for designing earthquake-resistant building structures. This condition worsens when buildings experience significant degradation in concrete strength, thereby reducing structural ductility. This study aims to evaluate the seismic performance of existing buildings designed under old regulations (SNI 1726:2002 and SNI 2847:2002) and exhibiting significant concrete strength degradation. The method used in this evaluation is based on ASCE 41-17 using a Tier 3 linear procedure with response spectrum analysis. The building evaluated is a 6-story laboratory building located at the University of Indonesia. This modeling was carried out using several concrete degradation scenarios (30, 25, 20, and 15 MPa). The parameters evaluated are structural drift and DCR using the BSE 2E earthquake level. Based on the global performance, there is an increase in structural drift in the x and y directions, so that the Life Safety (LS) performance limit of 2% is not met. Then, the DCR value increased for deformation-controlled and force-controlled actions, resulting in a higher percentage of beam and column components failing to meet the Life Safety (LS) performance target. For beam components, critical conditions for flexural and shear performance are found on the lower floors. For column components, critical conditions for flexural and axial performance are found on the lower floors. Meanwhile, critical conditions for shear performance are found on the middle floors. Therefore, critical elements requiring special attention can be properly identified, thereby facilitating the planning of structural strengthening.